GROWTH AND PRODUCTION OF SETARIA GRASS (Setaria splendida) FERTILIZED WITH DIFFERENT DOSAGE OF GOAT DEVELOPMENT AND DECOMPOSITION TIME - P. M. A., Gunantika; Witariadi, N. M.; Wirawan, W. (Jurnal Peternakan Tropika, 2023)
This study aims to determine the best dose and time of decomposition of goat manure fertilizer and the interaction on the growth and yield of setaria grass (Setaria splendida). The research was conducted at the Greenhouse, Sesetan Research Station, Faculty of Animal Husbandry, Udayana University on Jalan Raya Sesetan Gang Markisa. The study lasted for 3 months, using a completely randomized design (CRD) with a factorial pattern. The first factor was the decomposition time:no decomposition (W0), 2 weeks (W2), and 4 weeks (W4). The second factor consisted of fertilizer doses, namely D0: 0 tons ha-1, D1: 5 tons ha- 1, D2 :10 tons ha-1, D3: 15 tons ha-1 and D4: 20 tons ha-1. There were 15 treatment combinations and each treatment was repeated three times, so there were 45 experimental units. The variables observed were growth variables (plant height, number of tillers, number of leaves), production variables (dry weight of leaves, dry weight of stems, total dry weight of forage, and dry weight of roots), and plant growth characteristics variables (ratio of leaf dry weight with stem dry weight, ratio of total dry weight to root dry weight, and leaf area/pot). The results showed that there was an interaction between dosage treatment and decomposition time on stem dry weight variable. The dosage treatment affected the plant height variable, while the decomposition time treatment affected the stem dry weight variable, and leaf/pot area variable. It can be concluded that the decomposition time treatment 2 weeks and a dosage of 20 tons ha-1 gave the best results on the growth and yield of setaria grass (Setaria splendida). Keywords: decomposition, yield, goat manure, growth, Setaria splendida.